PRACTICE OF OUTDOOR LEARNING TO PROMOTING LEVEL COGNITIVE THINKING IN PHYSICS STUDENT - Nirwana, Nirwana; Rochman, Syaiful (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2019)
This study aims to improve cognitive thinking skills in physics courses. This research is a Classroom Action Research (CAR) which consists of three cycles. Each cycle consists of planning, observation, and reflection. The population of this study was students of the University of Bengkulu Physics Education. The research instruments used were observation and test sheets. The indicator of success is seen from the score of activity, that is if the cycle III> cycle II> cycle I and categorized well. Learning outcomes are said to increase if the average in cycle III> cycle II> cycle I. Absorption is said to increase when the cycle III> cycle II> cycle I. learning is said to be completed individually if the student value is ≥70 and completes classically if ≥ 85% students get a score of ≥70. The conclusion of this study is that it can improve learning outcomes in physics education students. The average score of student learning activities in the first cycle of 28 in sufficient categories, in the second cycle is to be 32 in the good category, in the third cycle is to be 35 in the good category. The application of this model can improve student learning processes, namely understanding the material with an average value of the first cycle of 64, the second cycle of 73.3 and the third cycle of 82.7. Student absorption of cycle I was 64%, cycle II was 73.3%, and cycle III was 82.7%, and learning completeness in cycle I was 65%, cycle II was 85% and cycle III was 100%.